The Impact of the Disclosure of "Pollution Control" Information on the Investors: "A Behavioral Field Experiment and a Market Reaction Investigation" - Belkaoui, Ahmed (Journal of Finance, 1974)
Ahmed Belkaoui, The Impact of the Disclosure of "Pollution Control" Information on the Investors: "A Behavioral Field Experiment and a Market Reaction Investigation", The Journal of Finance, Vol. 29, No. 5 (Dec., 1974), pp. 1586-1587